Super-hydrophobic modified thermochromic temperature control coating and preparation method thereof

By constructing a dual-layer structure of radiative cooling bottom layer and intelligent response layer, and utilizing thermochromic microcapsules and superhydrophobic surface modification, the adaptive control problem of building coatings in thermal management is solved, achieving efficient cooling and self-cleaning effects in all seasons, reducing energy consumption, and making it suitable for a variety of building substrates.

CN122628620APending Publication Date: 2026-08-25SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610807122.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing building coatings suffer from problems in thermal management, including static optical property defects, high energy consumption, complex operation, and insufficient functional integration. They are particularly difficult to achieve adaptive control in high-temperature summer and low-temperature winter environments.

Method used

A dual-layer structure of radiation cooling substrate and intelligent response layer is constructed. Thermochromic microcapsules are used as passive light-controlled switches, and combined with superhydrophobic surface modification, to achieve adaptive thermal management of the coating.

Benefits of technology

It achieves all-season adaptive thermal management, reduces building energy consumption, improves the coating's weather resistance and self-cleaning ability, is compatible with a variety of building substrates, and is convenient, economical and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application relates to the technical field of super-hydrophobic coating and self-adaptive thermal management, and particularly relates to a super-hydrophobic modified thermochromic temperature control coating and a preparation method thereof.A specific technical scheme is as follows: inspired by the self-adaptive color-changing temperature control mechanism of the skin of an angle lizard, a double-layer structure of a hydroxylated cerium dioxide enhanced radiation cooling bottom layer and a super-hydrophobic modified thermochromic phase change microcapsule intelligent response layer is constructed; a thermochromic phase change microcapsule is prepared by taking 20-30 DEG C phase change paraffin as a core material, crystal violet lactone-bisphenol A as a thermochromic system and melamine resin as a shell material, and after two-step super-hydrophobic modification of amination and fluorination, the thermochromic phase change microcapsule is compounded with hydrophobic silicon dioxide and epoxy resin to obtain an intelligent response layer coating, which is sprayed on the surface of the hydroxylated cerium dioxide / polyether sulfone radiation cooling bottom layer to be solidified to obtain a composite coating.The present application realizes efficient cooling of an outdoor building surface in summer, self-cleaning in a whole cycle, greatly reduces building energy consumption, has excellent weather resistance and durability, is convenient to construct and has significant engineering application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of superhydrophobic coatings and adaptive thermal management technology, specifically to a superhydrophobic modified thermochromic temperature-controlled coating and its preparation method. Background Technology

[0002] The surge in global energy consumption and the exacerbation of climate change have made thermal management of outdoor building surfaces a core pain point in the field of building energy conservation: In summer, the temperature of building surfaces after solar radiation can reach over 50°C, significantly increasing indoor air conditioning energy consumption. According to data from the China Building Energy Conservation Association, carbon emissions in urban and rural construction account for a high proportion, and building cooling energy consumption is an important component. In winter, building surfaces are prone to icing and frost, which not only damages the building structure but also easily causes safety hazards. At the same time, outdoor building surfaces are prone to dust accumulation and rainwater adhesion, leading to the rapid failure of various functional coatings.

[0003] Passive radiative cooling technology, as an energy-free cooling method, has become a research hotspot for building cooling. It achieves cooling by reflecting 0.3-2.5μm sunlight and radiating heat into space through an 8-13μm atmospheric transparent window. However, traditional radiative cooling coatings have static optical characteristic defects, namely the "supercooling effect" in low-temperature environments. Continuous heat dissipation in winter will increase heating energy consumption, and there is a lack of temperature adaptive regulation capability. Existing optically adjustable strategies, such as mechanically driven coatings and electro-optic devices, all rely on active stimulation or additional control, which have problems of low efficiency and complex operation, and cannot meet the actual needs of building energy conservation.

[0004] Thermochromic materials can achieve reversible optical changes with temperature, making them ideal materials for passive light control. However, existing thermochromic materials such as vanadium dioxide and perovskite have problems such as poor compatibility between phase change temperature and building surface, high encapsulation requirements, and easy degradation of outdoor performance. Phase change microcapsules can suppress temperature fluctuations through latent heat buffering, but their direct incorporation into coatings is prone to leakage and phase separation problems, and their integration with thermochromic and superhydrophobic functions is insufficient.

[0005] Inspired by the biomechanics of horned lizard skin's adaptive color-changing regulation of body temperature, this invention constructs a two-layer structure of "radiative cooling underlayer - intelligent response layer," using thermochromic microcapsules as passive light-controlled switches. When the temperature is below a certain range, the microcapsules appear dark, significantly increasing the coating's absorption rate of sunlight and actively raising the temperature through photothermal conversion. When the temperature is above this range, the microcapsules return to colorless, and the coating exhibits a high reflectivity, achieving efficient heat dissipation in conjunction with the underlying radiative cooling layer. Simultaneously, superhydrophobic surface modification endows the coating with anti-frost and self-cleaning capabilities. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a superhydrophobic modified thermochromic temperature-controlled coating and its preparation method. By constructing a dual-layer structure of a radiation cooling underlayer and a superhydrophobic modified thermochromic phase change microcapsule intelligent response layer, adaptive thermal management of outdoor building surfaces is achieved.

[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing thermochromic phase change microcapsules, comprising the following steps: (1) A thermochromic phase change material was prepared by melt blending phase change paraffin, crystal violet lactone and bisphenol A; (2) After mixing melamine, formaldehyde aqueous solution and deionized water, the pH is adjusted to 8-9, and after water bath reaction, melamine resin prepolymer solution is obtained. (3) Mix the thermochromic phase change material, emulsifier and deionized water, and emulsify under high speed stirring to form a stable oil-in-water emulsion, namely the thermochromic phase change material emulsion. (4) The melamine resin prepolymer solution from step (2) is dropped into the thermochromic phase change material emulsion from step (3), and the pH value of the reaction system is adjusted to weak acidity (pH 5-6). After the reaction is completed, the thermochromic phase change microcapsule suspension is obtained. The thermochromic phase change microcapsule suspension is filtered, washed, and dried to obtain the thermochromic phase change microcapsules.

[0008] Preferably, in step (1), the phase change temperature of the phase change paraffin is 20-30℃, and the mass ratio of crystal violet lactone, bisphenol A, and phase change paraffin is 1:4-6:50-1000.

[0009] Preferably, in step (2), the mass ratio of melamine, formaldehyde aqueous solution and deionized water is 1:2:16-40, and the mass fraction of formaldehyde aqueous solution is 37wt%; the mass ratio of the sum of the masses of melamine and formaldehyde aqueous solution to the mass ratio of phase change paraffin is 1:4-10.

[0010] Preferably, in step (3), the emulsifier is a 10wt% sodium polystyrene maleic anhydride aqueous solution, the amount of which is 6%-16% of the phase change paraffin, and the stirring speed is 800-1200 rpm.

[0011] Preferably, in step (4), the melamine resin prepolymer solution is dropped into the oil-in-water emulsion at a rate of 0.8-1.5 mL / min.

[0012] Correspondingly, a method for preparing superhydrophobic modified thermochromic microcapsules involves dispersing the prepared thermochromic phase change microcapsules in ethanol, ultrasonically mixing them until homogeneous, adding a silane coupling agent, stirring until homogeneous at room temperature, adding a fluorosilane modifier, reacting at room temperature, and then filtering and drying to obtain superhydrophobic modified thermochromic phase change microcapsules.

[0013] Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane (KH550), and the fluorosilane modifier is heptadecafluorodecyltrimethoxysilane (FAS-17). The mass ratio of the thermochromic phase change microcapsules to the volume ratio of the silane coupling agent, the fluorosilane modifier, and anhydrous ethanol is 1:0.1:0.1:10.

[0014] Correspondingly, a method for preparing a radiation cooling coating involves mixing and stirring polyethersulfone, hydroxylated cerium dioxide, N-methylpyrrolidone and ethanol to form a uniform dispersion, and then coating it onto the surface of a substrate to obtain a radiation cooling underlayer.

[0015] Preferably, the polyethersulfone has a mass fraction of 5 wt%, the hydroxylated cerium dioxide has a mass fraction of 50 wt%, the N-methylpyrrolidone has a mass fraction of 40 wt%, and the ethanol has a mass fraction of 5 wt%.

[0016] Correspondingly, the preparation process of hydroxylated cerium dioxide is as follows: cerium ammonium nitrate and urea are dissolved in deionized water, and after hydrothermal reaction, hydroxylated cerium dioxide is obtained.

[0017] Preferably, the mass ratio of cerium ammonium nitrate to urea is 0.85-0.9:1.

[0018] Correspondingly, a method for preparing a superhydrophobic modified thermochromic temperature-controlled coating involves dispersing superhydrophobic modified thermochromic phase change microcapsules and hydrophobic silica particles in an organic solvent, adding epoxy resin and a curing agent to obtain a smart responsive layer coating, spraying it onto the surface of a radiation-cooled substrate by spraying, and curing it to obtain a composite coating.

[0019] Preferably, the organic solvent is one of hexane, ethyl acetate and butyl acetate, and the curing agent is one or more of T31, D230, methylhexahydrophthalic anhydride and DMP30; The superhydrophobic modified thermochromic phase change microgel, hydrophobic silica particles, epoxy resin, curing agent and organic solvent have a mass-to-volume ratio of 0.25-1:0.05:1:0.1-0.3:20, a spraying pressure of 0.3 MPa, a spraying distance of 20-30 cm, a dry film thickness of 80-120 μm, a curing temperature of 30-60℃, and a curing time of 4-24 h.

[0020] Correspondingly, a superhydrophobic modified thermochromic temperature-controlled coating was prepared.

[0021] The present invention has the following beneficial effects: 1. Inspired by the color-changing temperature control mechanism of the horned lizard, thermochromic microcapsules act as passive light-controlled switches, autonomously switching between color and optical performance at temperatures ranging from 20℃ to 30℃. At high temperatures, the colorless design adapts to high reflectivity and radiative cooling, reducing the building surface temperature by 10-15℃ without energy consumption. At low temperatures, the color enhances photothermal absorption and mitigates the "supercooling effect" through latent heat buffering via phase change, achieving all-season adaptive thermal management and solving pain points such as high temperature, icing, dust accumulation, and high energy consumption in outdoor buildings.

[0022] 2. The thermochromic phase change microcapsules are modified in two steps: amination and fluorination, which takes into account both superhydrophobic properties and interfacial bonding. The melamine resin shell material prevents leakage of the phase change core material, and hydroxylated cerium dioxide and polyethersulfone form a stable porous radiation cooling bottom layer through hydrogen bonding.

[0023] 3. The coating of this invention integrates four major functions: passive radiation cooling, thermochromic light control, phase change latent heat buffering, and superhydrophobic anti-icing self-cleaning. It achieves reversible color change at 20℃-30℃, has a water contact angle of >150°, solar reflectivity of >96%, and mid-infrared emissivity of >0.9. It can achieve efficient cooling of outdoor building surfaces in summer, full-cycle self-cleaning, significantly reduce building energy consumption, has excellent weather resistance and durability, is easy to construct, and has significant engineering application value.

[0024] 4. The radiative cooling base layer is scraped and the intelligent response layer is sprayed in this invention, which is convenient to construct and suitable for various building substrates such as concrete and color steel plates. The raw materials are readily available and the cost is controllable. There is no VOC release and it is environmentally friendly. It can significantly reduce the energy consumption of building cooling / heating and improve the durability of buildings, providing an innovative solution for building energy conservation, and has economic, environmental and social value. Attached Figure Description

[0025] Figure 1 Optical images of thermochromic phase change materials and thermochromic phase change microcapsules before and after color change; Figure 2 The image shows the contact angle of the composite coating prepared in Example 1. Figure 3 SEM images of thermochromic phase change microcapsules; Figure 4 DSC curves for PW, RTPCM, and RTPCM; Figure 5 DSC curves of thermochromic phase change microcapsules prepared at different emulsification speeds; (a) solidification curve, (b) melting curve; Figure 6 The reflectivity of the composite coating prepared in Example 1 in the solar radiation band; Figure 7The composite coating prepared in Example 1 has a high infrared reflectivity; Figure 8 This is the real-time temperature change curve of the composite coating. Detailed Implementation

[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] Unless otherwise specified, the technical means used in the implementation examples are conventional means well known to those skilled in the art.

[0028] This invention provides a method for preparing a superhydrophobic modified thermochromic temperature-controlled coating, comprising the following steps: (1) Preparation of thermochromic phase change microcapsules 1.1 Preparation of thermochromic phase change materials Weigh crystal violet lactone, bisphenol A, and phase change paraffin into a beaker, and magnetically stir at 500 rpm for 10-15 minutes at 90°C until the system is clear and transparent to obtain a thermochromic phase change material.

[0029] The phase change paraffin has a phase change temperature of 20-30℃, and the crystal violet lactone, bisphenol A, and phase change paraffin are in a mass ratio of 1:4-6:50-1000.

[0030] 1.2 Preparation of melamine resin prepolymer Melamine, 37wt% formaldehyde aqueous solution and deionized water are mixed, and triethanolamine is added to adjust the pH to 8-9. The mixture is then reacted in a 70℃ water bath for 15-20 minutes to obtain a transparent melamine resin prepolymer solution.

[0031] The mass ratio of melamine, 37wt% formaldehyde aqueous solution, and deionized water is 1:2:16-40. The mass ratio of the sum of the masses of melamine and 37wt% formaldehyde aqueous solution to the mass ratio of phase change paraffin is 1:4-10.

[0032] 1.3 Preparation of oil-in-water emulsions The thermochromic phase change material, emulsifier, and 100 mL of deionized water were mixed and emulsified at high speed at 55°C for 2 hours to form a stable oil-in-water emulsion. The emulsifier was a 10 wt% aqueous solution of sodium polystyrene maleic anhydride, and the amount used was 6%-16% of the phase change paraffin (calculated according to the actual mass of sodium polystyrene maleic anhydride). The stirring speed was 800-1200 rpm.

[0033] (1.4) Synthesis of microcapsules At 350 rpm and 55 ℃, the melamine resin prepolymer solution was dropped into the oil-in-water emulsion at a rate of 0.8-1.5 mL / min. After the addition was complete, the pH was adjusted to 5-6 with 10 wt% glacial acetic acid, and the reaction was carried out at 75 ℃ and 500 rpm for 3 h. After the reaction was completed, the reaction was terminated by neutralization with triethanolamine to obtain a thermochromic phase change microcapsule suspension. After vacuum filtration, repeated washing with anhydrous ethanol and deionized water three times, and drying at 35 ℃ for 24 h, the thermochromic phase change microcapsules were obtained.

[0034] (2) Superhydrophobic modification of thermochromic phase change microcapsules: Thermochromic phase change microcapsules were dispersed in ethanol, sonicated for 20 min, a silane coupling agent was added, stirred at room temperature for 60 min, a fluorosilane modifier was added, and reacted at room temperature for 3 h. After filtration and drying at 80 °C for 24 h, superhydrophobic modified thermochromic phase change microcapsules were obtained.

[0035] The silane coupling agent is 3-aminopropyltriethoxysilane, the fluorosilane modifier is heptadecafluorodecyltrimethoxysilane (FAS-17), and the mass ratio of the thermochromic phase change microcapsules to the volume ratio of the silane coupling agent, the fluorosilane modifier, and anhydrous ethanol is 1:0.1:0.1:10.

[0036] (3) Preparation of hydroxylated cerium dioxide enhanced radiation cooling substrate: 3.1 Preparation of hydroxylated cerium dioxide Cerium ammonium nitrate and urea were dissolved in deionized water and subjected to a hydrothermal reaction at 180-220℃ for 16-20 h. After natural cooling, the precipitate was collected by centrifugation, washed three times each with deionized water and ethanol, and dried under vacuum at 80℃ to obtain hydroxylated cerium dioxide nanoparticles. The mass ratio of cerium ammonium nitrate to urea was 0.85-0.9:1, and the solid-liquid ratio was controlled at 1 g: 5-12 mL.

[0037] 3.2 Preparation of hydroxylated cerium dioxide enhanced radiation cooling substrate A precursor solution was prepared by mixing polyethersulfone, hydroxylated cerium dioxide, N-methylpyrrolidone, and ethanol, and stirred at 500 rpm for 12 h to form a uniform dispersion. The precursor solution was then coated onto the surface of a building concrete substrate with a wet film thickness of 1 mm. After standing at room temperature for 24 h, a porous network structure was formed through solvent evaporation / phase transformation, resulting in a radiation cooling underlayer.

[0038] The polyethersulfone has a mass fraction of 5 wt%, the hydroxylated cerium dioxide has a mass fraction of 50 wt%, the N-methylpyrrolidone has a mass fraction of 40 wt%, and the ethanol has a mass fraction of 5 wt%.

[0039] (4) Preparation of the double-layer composite coating: Superhydrophobic modified thermochromic phase change microcapsules and hydrophobic silica particles were dispersed in an organic solvent, and epoxy resin and curing agent were added to prepare a smart responsive layer coating. The coating was then sprayed onto the surface of a radiation-cooled substrate and cured to obtain a composite coating.

[0040] The organic solvent is one of hexane, ethyl acetate and butyl acetate, the adhesive is epoxy resin, and the curing agent is one or more of T31, D230, methylhexahydrophthalic anhydride and DMP30.

[0041] Superhydrophobic modified thermochromic phase change microcapsules: hydrophobic silica particles: epoxy resin: curing agent: organic solvent = 0.25-1:0.05:1:0.1-0.3:20, w / v. Spraying pressure: 0.3 MPa; spraying distance: 20-30 cm; dry film thickness: 80-120 μm; curing temperature: 30-60℃; curing time: 4-24 h.

[0042] The present invention will be further described below with reference to specific embodiments.

[0043] Example 1 A method for preparing a superhydrophobic modified thermochromic temperature-controlled coating, comprising the following steps: I. Preparation of Thermochromic Phase Change Microcapsules (1) Preparation of thermochromic phase change material: Weigh 0.075g crystal violet lactone, 0.45g bisphenol A and 15g 23℃ phase change paraffin (PW) into a beaker, stir magnetically at 500rpm for 15min at 90℃ until the system is clear and transparent, and obtain thermochromic phase change material (RTPCM).

[0044] (2) Preparation of melamine resin prepolymer: Mix 0.625g melamine, 1.25g 37wt% formaldehyde aqueous solution and 20mL deionized water, add triethanolamine to adjust pH to 8-9, and react at a constant temperature of 70℃ for 15min to obtain a transparent melamine resin prepolymer solution.

[0045] (3) Preparation of oil-in-water emulsion: 15g of the above thermochromic phase change material, 18g of 10wt% sodium polystyrene maleic anhydride aqueous solution and 100mL of deionized water were added to a three-necked flask and emulsified at 1000rpm at 55℃ for 2h to form a stable oil-in-water emulsion.

[0046] (4) Synthesis of thermochromic phase change microcapsules: melamine resin prepolymer solution was added to emulsion at a rate of 1 mL / min at 350 rpm and 55 ℃. After the addition was complete, the pH was adjusted to 6 with 10 wt% glacial acetic acid. The reaction was carried out at 75 ℃ and 500 rpm for 3 h. The reaction was terminated by neutralization with triethanolamine. After vacuum filtration, washing three times with anhydrous ethanol and deionized water, and drying at 35 ℃ for 24 h, thermochromic phase change microcapsules (RTMPCM) were obtained.

[0047] II. Preparation of Superhydrophobic Modified Thermochromic Phase Change Microcapsules Take 2.0 g of the thermochromic phase change microcapsules prepared in step one, disperse them in 20 mL of ethanol, and sonicate for 20 min; add 200 μL of 3-aminopropyltriethoxysilane (KH550), stir at room temperature for 60 min to introduce -NH2 active sites; continue to add 200 μL of heptadecafluorodecyltrimethoxysilane (FAS-17), stir at room temperature for 180 min to graft fluorocarbon chains; filter and dry at 80 °C for 24 h to obtain superhydrophobic modified thermochromic phase change microcapsules.

[0048] III. Preparation of Hydroxylated Cerium Dioxide Enhanced Radiation Cooling Substrates (1) Preparation of hydroxylated cerium dioxide: 3.19 g of cerium ammonium nitrate and 3.61 g of urea were dissolved in 40 mL of deionized water and transferred to a 50 mL polytetrafluoroethylene-lined high-pressure reactor. The reaction was carried out at 200 °C for 18 h. After natural cooling, the precipitate was collected by centrifugation, washed three times each with deionized water and ethanol, and dried under vacuum at 80 °C to obtain hydroxylated cerium dioxide nanoparticles.

[0049] (2) Preparation of precursor solution: Prepare precursor solution with 5wt% polyethersulfone, 50wt% hydroxylated cerium dioxide, 40wt% N-methylpyrrolidone and 5wt% ethanol, and stir at 500rpm for 12h to form a uniform dispersion.

[0050] (3) Film formation by scraping: The precursor liquid is scraped onto the surface of the building concrete substrate with a wet film thickness of 1 mm. After standing at room temperature for 24 hours, a porous network structure is formed through solvent evaporation / phase transformation, resulting in a radiation cooling underlayer.

[0051] IV. Preparation of Adaptive Thermally Regulated Superhydrophobic Composite Coatings 0.8g of the superhydrophobic modified thermochromic phase change microcapsules obtained in step two and 0.05g of 20nm hydrophobic silica particles were ultrasonically dispersed in 20mL of ethyl acetate; 1g of E51 epoxy resin and 0.3g of D230 curing agent were added, and the mixture was stirred at room temperature for 20min to obtain a smart responsive layer coating; the coating was sprayed onto the surface of the radiation-cooled substrate obtained in step (3) at a spraying pressure of 0.3MPa and a spraying distance of 25cm, with a dry film thickness of 100μm; the coating was cured at 60℃ for 4h to obtain a composite coating. Figure 2As shown, the composite coating prepared by the modified thermochromic phase change microcapsules has a static water contact angle of 156° and a roll-off angle of 4°.

[0052] Result characterization: (1) Images of the thermochromic phase change material and the thermochromic phase change microcapsules before and after the color change are shown below. Figure 1 As shown, both exhibit a uniform deep blue color when the temperature is below 20℃; when the temperature rises above 30℃, both rapidly transform into a colorless and transparent state. The color change process is reversible and there is no obvious residual color difference. Testing revealed that the color-changing temperature range is controlled between 20-30℃, highly matching the adaptive temperature control requirements of building surfaces; the color difference value ΔE=85.8 indicates high color contrast and significant optical control effect; after 50 cycles of hot and cold color-changing tests, the color difference value remained at 79, indicating that the melamine resin shell effectively protects the internal thermochromic system and exhibits excellent cycle stability.

[0053] (2) The DSC curves of PW, RTPCM and RTPCM are as follows: Figure 4 As shown in Table 1 below, the thermal properties are as follows: Figure 4 As can be seen from the data, PW, RTPCM, and RTPCM all exhibit single and sharp melting and solidification peaks, with no extraneous peaks, indicating that all three have good phase change reversibility and thermal stability, and no thermal decomposition or component separation occurs. Table 1 shows that after introducing the crystal violet lactone and bisphenol A thermochromic system, the thermal performance of RTPCM is almost not significantly reduced compared to pure PW, indicating that the addition of the thermochromic components does not significantly affect the heat storage capacity of the phase change paraffin. After encapsulation with melamine resin shell, the phase change core material encapsulation rate of RTPCM is 79.48%, with good encapsulation effect, and the phase change temperature remains stable within the target range of 20-30℃, meeting the adaptive temperature control requirements.

[0054] Table 1 Thermal properties of PW, RTPCM and RTPCM

[0055] (3) SEM image of the thermochromic phase change microcapsules prepared in step one is shown below. Figure 3 As shown in the figure, the prepared thermochromic phase change microcapsules have a regular spherical structure with a particle size of 3-5 μm. The particles are evenly distributed, and the surface is smooth and dense. There are no obvious damages, depressions, adhesions, or shell detachment. This indicates that the melamine resin shell prepared by in-situ polymerization is complete and continuous, which can effectively prevent leakage of the internal phase change core material. At the same time, it ensures the structural integrity of the microcapsules in the subsequent superhydrophobic modification and coating preparation process.

[0056] (4) The DSC curves of the thermochromic phase change microcapsules prepared at different emulsification speeds in step (3) of step one are as follows: Figure 5As shown in Table 2, the thermal performance parameters are as follows. The results show that as the emulsification speed increases to 1000 rpm, the latent heat of fusion and the latent heat of solidification of the microcapsules gradually increase, correspondingly increasing the core material encapsulation efficiency from 71.52% to 78.18%. When the speed continues to increase to 1200 rpm and 1400 rpm, the latent heat of fusion of the microcapsules decreases to 130.2 J / g and 124.7 J / g, respectively, and the encapsulation efficiency also decreases to 66.16% and 64.34%. This is because excessively low emulsification speeds cannot fully disperse the oil phase into fine, uniform droplets, resulting in excessively large and unevenly distributed microcapsule particles, making it difficult for the shell material to completely encapsulate the core material, thus reducing the encapsulation efficiency. Conversely, excessively high emulsification speeds cause the droplets to become too small, making them prone to aggregation and demulsification during polymerization, which also leads to core material leakage and a decrease in encapsulation efficiency.

[0057] Table 2 Thermal performance parameters of thermochromic phase change microcapsules at different emulsification speeds

[0058] (5) The reflectivity of the composite coating prepared in step four in the solar radiation band is as follows: Figure 6 As shown, the results indicate that the composite coating exhibits extremely high reflectivity across the entire solar radiation band from 300 to 2500 nm, with a maximum reflectivity of approximately 96.5%. This effectively reflects most of the solar radiation energy, preventing the building surface from heating up rapidly due to absorbing sunlight.

[0059] Mid-to-high infrared reflectivity, such as Figure 7 As shown, the results indicate that within the wavelength range corresponding to the atmospheric window (8-13 μm), the coating exhibits relatively uniform and moderate emission characteristics. Specifically, the average reflectance is approximately 8.90% (emissivity approximately 91.1%) in the 8-9 μm range, approximately 9.34% (emissivity approximately 90.7%) in the 9-10 μm range, approximately 10.02% (emissivity approximately 90.0%) in the 10-11 μm range, approximately 11.63% (emissivity approximately 88.4%) in the 11-12 μm range, and approximately 13.67% (emissivity approximately 86.3%) in the 12-13 μm range. The emissivity in the 8-11 μm range at the forefront of the atmospheric window is ideal, ranging from 90% to 91%.

[0060] The real-time temperature change curve of the composite coating is as follows: Figure 8As shown in the figure. The results show that when the air temperature fluctuates between 20-40℃, the surface temperature of the uncoated building concrete substrate rises rapidly with increasing solar radiation intensity, reaching a maximum of about 41℃; while the surface temperature of the substrate coated with the composite coating of this invention changes more gradually, with a maximum temperature of about 25.8℃. Compared with the uncoated substrate, the maximum temperature drop is about 15℃, and it is only about 1.5℃ higher than the highest air temperature at the same time, showing a significant cooling effect. This result verifies the synergistic effect of high solar reflectance and high infrared radiation cooling of the coating at high temperatures. At the same time, the latent heat buffering effect of the phase change microcapsules further suppresses the drastic temperature fluctuations, improves temperature control stability, and can effectively reduce the energy consumption of building indoor air conditioning.

[0061] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing a superhydrophobic modified thermochromic temperature-controlled coating, characterized in that: Includes the following steps: (1) Mix the thermochromic phase change material, emulsifier and deionized water, and emulsify under high speed to form an oil-in-water emulsion; (2) The melamine resin prepolymer solution was added dropwise to the oil-in-water emulsion. After the addition was complete, the pH was adjusted to 5-6. After the reaction was completed, thermochromic phase change microcapsules were obtained. (3) The thermochromic phase change microcapsules were modified by two steps of amination and fluorination to obtain superhydrophobic modified thermochromic phase change microcapsules, which were then mixed with hydrophobic silica particles, epoxy resin, curing agent and organic solvent to prepare smart response layer coating. (4) The intelligent response layer coating is sprayed onto the surface of the radiation cooling substrate and cured to obtain a composite coating.

2. The preparation method according to claim 1, characterized in that: In step (1), the emulsifier is a 10wt% sodium polystyrene maleic anhydride aqueous solution, and the amount used is 6%-16% of the phase change paraffin based on the mass of sodium polystyrene maleic anhydride, with a stirring speed of 800-1200 rpm.

3. The preparation method according to claim 1, characterized in that: In step (1), the preparation process of the thermochromic phase change material is as follows: the thermochromic phase change material is prepared by melt blending phase change paraffin, crystal violet lactone and bisphenol A.

4. The preparation method according to claim 3, characterized in that: The mass ratio of crystal violet lactone, bisphenol A, and phase change paraffin is 1:4-6:50-1000.

5. The preparation method according to claim 1, characterized in that: In step (2), the melamine resin prepolymer solution is dropped into the oil-in-water emulsion at a rate of 0.8-1.5 mL / min.

6. The preparation method according to claim 1 or 5, characterized in that: The preparation process of the melamine resin prepolymer solution is as follows: melamine, formaldehyde aqueous solution and deionized water are mixed, the pH is adjusted to 8-9, and after water bath reaction, melamine resin prepolymer solution is obtained.

7. The preparation method according to claim 6, characterized in that: The mass ratio of melamine, formaldehyde aqueous solution and deionized water is 1:2:16-40, the mass fraction of formaldehyde aqueous solution is 37wt%, and the mass ratio of the sum of the masses of melamine and formaldehyde aqueous solution to the mass of phase change paraffin is 1:4-10.

8. The preparation method according to claim 1, characterized in that: In step (3), the mass-volume ratio of the superhydrophobic modified thermochromic phase change microgel, hydrophobic silica particles, epoxy resin, curing agent and organic solvent is 0.25-1:0.05:1:0.1-0.3:

20.

9. The preparation method according to claim 1, characterized in that: In step (4), the preparation process of the radiation cooling underlayer is as follows: polyethersulfone, hydroxylated cerium dioxide, N-methylpyrrolidone and ethanol are mixed and stirred to form a uniform dispersion, and then coated onto the surface of the substrate to obtain the radiation cooling underlayer; The preparation process of the hydroxylated cerium dioxide is as follows: cerium ammonium nitrate and urea are dissolved in deionized water and subjected to a hydrothermal reaction to obtain hydroxylated cerium dioxide; the mass ratio of cerium ammonium nitrate to urea is 0.85-0.9:

1.

10. A superhydrophobic modified thermochromic temperature-controlled coating prepared by the preparation method according to any one of claims 1-9.